1975
DOI: 10.1128/jvi.15.2.253-258.1975
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of adenovirus replication in simian cells in the absence of a helper virus by pretreatment of the cells with iododeoxyuridine

Abstract: Pretreatment of African green monkey kidney cells with 50 ,ug of 5'-iododeoxyuridine (IUdR) per ml can modify their susceptibility to the replication of human adenovirus type 7 in the absence of simian virus 40 (SV40) although this enhancement of adenovirus replication is not as efficient as that of the helper SV40 virus. Since the number of infectious centers remains unchanged after IUdR pretreatment whereas the burst size of virus from each infected cell increases, the IUdR appears to allow each infected cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1977
1977
1986
1986

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…bThe results during acute infection are essentially the same as those published by Staal and Rowe (23) and Jerkofsky and Rapp (10) and serve as controls.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…bThe results during acute infection are essentially the same as those published by Staal and Rowe (23) and Jerkofsky and Rapp (10) and serve as controls.…”
Section: Resultsmentioning
confidence: 65%
“…One possible mechanism of apparent persistence could consist of low-level cell-to-cell infections. It has previously been shown that IUdR can enhance the yield of adenovirus during nonpermissive infection of monkey cells (10,23). The mechanism of this enhancement is unknown.…”
Section: Nofluorescencementioning
confidence: 99%
“…Although the virus appeared to persist for a greater length of time in the infected cells, it did not increase above input level. It has been reported by a number of laboratories that pretreatment of cells with thymidine analogues, such as bromodeoxyuridine and 5iodo-2'-deoxyuridine (IUdR), will enhance infectivity of lytic virus infections (4,6,11,13,14,16). To determine whether pretreatment of F265 cells with IUdR might render them more susceptible to infection with CMV, the following study was initiated.…”
Section: Resultsmentioning
confidence: 99%
“…on September 25, 2020 by guest http://jvi.asm.org/ Downloaded from synthesizing T-antigen was not significantly changed by MC. This observation should be compared with the results obtained with IUdR, which enhances the growth of adenovirus 7 and SV40 upon treatment of cells semipermissive or permissive for these viruses (3,(10)(11)(12). In these two cases, it has been shown that IUdR pretreatment stimulates the percentage of T-antigensynthesizing cells and acts at a step preceding the expression of early viral functions.…”
Section: Notes Hours Ater Infectionmentioning
confidence: 97%